PRINCIPALS’ REWARD MANAGEMENT STRATEGIES AS A CORRELATE TO STAFF PERFORMANCE IN SECONDARY SCHOOLS IN DELTA STATE, NIGERIA - Nwaozor, Henry Osedebe; Thompson, Chidinma Chinenye (UNIZIK Journal of Educational Management and Policy, 2019)
The study was designed to find out the principals’ reward management strategies as a correlate to staff performance in Oshimili South Local Government Area of Delta State of Nigeria. The study adopted the descriptive research design. A 24- item structured questionnaire was developed by the researcher from the four research questions formulated to elicit data for this study. The population used for the study is made up of 697 staff selected from five private secondary schools and five public secondary schools in Oshimili South Local Government Area. A sample of twenty-five percent (167 respondents) was selected from the population for final study. Data were collected for the study through the administration of validated questionnaire to the respondents. The reliability of the instrument was determined using the test re-test method in which a correlation coefficient of 0.86 was obtained. Mean statistics and standard deviations were used to answer the research questions while the z-test statistic was used to test the hypothesis at 0.05 level of significance. The study revealed that principals’ reward management strategies in the form of pay base rewards, benefits rewards, carrier incentive rewards, and non-financial rewards correlate staff job performance. It was concluded that proper application of reward management strategies enhance staff performance but inadequate application of relevant reward management strategy will hamper staff performance and ultimately students’ academic achievement. It was therefore recommended among others that school principals and proprietors/proprietresses should be armed with adequate knowledge of various reward management strategies through seminars and in-service training in order to apply them intelligibly for maximum staff performance in schools.